Opioid-free Anesthesia Technique in Laparoscopic Hysterectomy: A Case Report - Islami Monika, Tesha; Sukmapradipta, Michael; Jasmine, Nabila; Antonius, Jonathan; Sulistio, Maria Edith (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2026)
Background: The use of opioid-free anesthesia techniques is increasingly recognized in efforts to reduce the risk of opioid-related postoperative side effects. Case: This case report describes the use of opioid-free anesthesia technique in laparoscopic hysterectomy in a 50-year-old woman with multiple myomas. The patient had a history of fentanyl allergy and was classified as ASA I. Anesthesia induction was performed with a combination of dexmedetomidine, ketamine, and rocuronium, maintained with sevoflurane, rocuronium, and lidocaine. The patient did not experience any complications during postoperative monitoring.Discussion: This case highlights that an opioid-free anesthesia approach can be safely implemented in patients with opioid allergies. The combination of dexmedetomidine, ketamine, and lidocaine provides adequate analgesia and hemodynamic stability, supporting its role as an effective alternative to opioid-based anesthesia Conclusion: This anesthesia technique demonstrates good pain control without the use of opioids and minimizes opioid-related side effects